Maracas Bay, Trinidad, B.W.I. - Sobrian, C. (Art Photo Studio, Trinidad, 2009)
The road leading to Maracas Bay through the mountains and off in the distance, the ocean waters at the base of the mountains. The Postcard is addressed to Miss Leslie Lapue and Miss B. Cooley, Meadville, Penn., U.S.A. Affixed to the postcard is a Swedish 55 öre stamp, postmarked January 17, 1964. Postcard number Rev. 8-61 83276.
Colour: Coloured; Style: Landscape; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Bays--Trinidad and Tobago; Beaches--Trinidad and Tobago; Mountain roads--Trinidad and Tobago; 1964; Automobiles--Trinidad and Tobago; Bathing beaches--Trinidad and Tobago; Maracas Bay